Turkish adaptation of the binge-watching addiction questionnaire (bwaq): a study of validity and reliability - Demirbaş, Elif; Irmak, Hatice Selin (Journal of Dependence, 2024)
Objective: This study aims to analyze the validity and reliability of the Binge-Watching Addiction Questionnaire by making its Turkish adaptation.Method: The sample of the study consists of 446 students, who are studying at a foundation university in Istanbul, in the field of health, who voluntarily agreed to participate in the research. The data of the study were collected through the "Personal Information Form", the "The Binge-Watching Addiction Questionnaire" and "Binge-Watching Engagement and Symptoms Questionnaire". A language adaptation of the Binge-Watching Addiction Questionnaire was made, and internal consistency, item-total score reliability coefficient, and two-half test reliability were examined for reliability study; Explanatory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) to reveal construct validity; For criterion-related validity, analysis was performed with a similar scale.Results: As a result of the factor analysis, it was determined that the Binge-Watching Addiction Questionnaire could be used in four dimensions as it was in the original scale. It was found that the internal consistency coefficient of the scale, whose mean score was 25.26±13.28, was .903, and the item-total correlation coefficients varied between .322 and .656. As a result of the analysis for criterion-related validity, a statistically significant positive correlation was observed between the two scales (r=.298, p
Keywords: Binge-watching; addiction; scale adaption; validity; reliability